The Legacy of Early Insecurity Histories in Shaping Adolescent Adaptation to Interparental Conflict. Issue 1 (3rd May 2013) - Davies, Patrick T.; Sturge‐Apple, Melissa L.; Bascoe, Sonnette M.; Cummings, E. Mark
<x xml:space="preserve">Abstract</x> This study tested whether the mediational pathway involving interparental conflict, adolescent emotional insecurity, and their psychological problems was altered by their earlier childhood histories of insecurity. Participants included 230 families, with the first of the five measurement occasions occurring when children were in first grade (Mage = 7 years). Results indicated that interparental conflict was associated with increases in adolescent emotional insecurity that, in turn, predicted subsequent increases in their psychological problems. Childhood insecurity predicted adolescent maladjustment 5 years later even after considering contemporaneous family experiences. Moderator findings revealed that adolescents with relatively higher levels of insecurity in childhood evidenced disproportionately greater and reduced levels of insecurity in the context of high and low levels of interparental conflict, respectively.